(E)-1-(3-Bromophenyl)-3-(3-fluorophenyl)prop-2- en-1-one - Rajendraprasad, S.; Chidan Kumar, C. S.; Ching, Kheng Quah; Chandraju, S.; Lokanath, N. K.; Naveen, S.; Warad, Ismail (International Union of Crystallography, 2017)
In the title compound, C15H10BrFO, the olefinic double bond adopts an E conformation. The molecule is non-planar as seen by the dihedral angle of 48.92 (11)° between the bromophenyl and fluorophenyl rings. The carbonyl group is twisted from the plane of the bromophenyl ring and the olefinic double bond. The trans conformation of the C=C double bond in the central enone group is confirmed by the C—C=C—C torsion angle of −165.7 (2)°.